Motivation and Challenges Among Indonesian Muslim Women Entrepreneurs in Small and Medium Enterprises (SMEs): A Qualitative Study - Azmi, I.A.G.; Basir, S.A. (American Scientific Publishers, 2016)
This paper aims to examine the motivation and challenges of Muslim women entrepreneurs in Indonesian SMEs. By using qualitative method, ten Muslim women entrepreneurs were interviewed in Indonesian SMEs around Jakarta, the capital city of Indonesia. Later, thematic analysis was conducted on the information obtained based on the types of motivation and challenges. It is found out that majority are motivated to do business in order to support their husbands and families, to earn additional income and to provide for poor people. They also have other motivating factors such as strategic location, good market demand and advice, own and workers’ skills, good products, good customer relation, prior training, accessible raw material and supportive government policies. Meanwhile, the challenges found are lack of customers, customer attitude, defrauded wholesalers, unsatisfactory infrastructure, lack of education and skills, deficient business loans, competition, lack of supplier confidence and family issues.